(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to optimise ball-related scenarios. A total of twenty-four U18 inter-league players participated in the randomised entry-exit evaluation tests and the training protocol, forming two age-specific groups: U18 (n=12) and U17 (n=12). The results of countermovement jump (CMJ) tests showed a significant difference between pre- and post-protocol measurements. The Rate of Perceived Exertion (RPE) index indicated a slight decline in the U17 group compared to a moderate decline in the U18 group. The dominant force corresponds to an equivalent field density of 101±13 m² per player (according to the Nick BROAD model), confirming the impact of our gameplay on neuromuscular aspects. Thus, training with a contextualised 2v2 game effectively enhances CMJ performance.